Trends in Philippine Linguistics: Papers of the First Philippine Linguistics Congress - Malicsi, Jonathan (The Archive; 1983: Trends in Philippine Linguistics: Papers of the First Philippine Linguistics Congress, 2025)
Indeed it seems like “better late than never” as this set of ten papers finally gets published five years after they were read at the First Philippine Linguistics Congress in May 1978. But the five years since, rather than diminish the import of the papers, have even proven their value as baseline references for theoretical and applied linguistics in the Philippines.   The First Philippine Linguistics Congress was organized primarily for such—the presentation of linguistic studies which reflect scientific research to date and upon which linguists working on Philippine languages could build conceptually towards more incisive and more comprehensive studies. With the Second Congress the tradition was set, and now, the holding of the Congress has become a continuing commitment of the Department of Linguistics and Asian Languages of UP to the growth of Philippine Linguistics.